Climate change - Wong, Kaufui Vincent (New York, [New York] (222 East 46th Street, New York, NY 10017) : Momentum Press, 2016)
Climate Change is a collection of a number of papers as well as chapters about the science of the subject. This collection is meant to inflame and excite conversation among engineers, scientists, and society at large. It would serve as a catalyst for a three-credit course, as a relatively new engineering subject, for both engineering and nonengineering university students. As university education develops to better prepare future leaders to appreciate science, technology, engineering, and mathematics, engineering courses for a mix of engineering and nonengineering majors are essential and so is the requirement for worthy textbooks. This monograph intends to be one of the useful tools available on this timely topic. The wide range of topics includes climate change and theories, the second law of thermodynamics, the global greenhouse effect, anthropogenic heat release, evidence around us owing to environmental change, sea level rise, jungles and forests, heat islands, atmospheric carbon dioxide removal via technology, nanotechnology, other innovations in response to climate change, and the energy-water-food nexus.
15. A balanced view -- Index.
Includes bibliographical references and index.
Also available in print.
Mode of access: World Wide Web.
System requirements: Adobe Acrobat reader.
Title from PDF title page (viewed on January 27, 2016).
Keywords: Climatic changes; air; anthropogenic heat release; carbon dioxide; energy-water-food nexus; environment; greenhouse effect; heat islands; jungles; nanotechnology; sea level rise; sun; technology; thermodynamics; water; weather